Caesarean section in developing countries - Kwawukume, E.Y. (Best Practice and Research: Clinical Obstetrics and Gynaecology, 2001)
In developing countries, obstetric practice, including the performance of caesarean section, is complicated by problems that are no longer seen in developed countries. The various indications for caesarean section might be the same but the operation is often technically more difficult to perform in developing areas. Developing countries lack resources. This chapter highlights the problems encountered in the developing world. Because cephalopelvic disproportion is one of the main indications for performing caesarean section in our subregion, the technique of delivery of the impacted fetal head is discussed and alternatives to caesarean section are also suggested. The current view on myomectomy at caesarean section is described; including the technique of bloodless myomectomy at caesarean section. It is hoped that, with the training of postgraduate doctors in anaesthesia and obstetrics, the delivery of obstetric care will be accessible to rural areas in the developing world.
Keywords: Caesarean section; Developing countries